Study on chemical constituents of piper sarmentosum stems / Intan Munirah Amran - Amran, Intan Munirah (Faculty of Applied Sciences, 2017)
Piper sarmentosum or commonly called 'kaduk' in Malaysia is belong to Piperaceae family. It is well known as the traditional medicinal herbs because it contains a variety of active chemical constituents. This study describes the extraction, isolation and characterization of the chemical constituents from stems of P. sarmentosum. The stems of P. sarmentosum were collected at village area around Perak, Malaysia. The stems of P. sarmentosum were extracted by hexane solvent followed by chloroform solvent and ethanol solvent. Each extracts were concentrated and yielded 2.49% of hexane crude extract, 1.84% of chloroform crude extract and 4.03% ethanol crude extract. The qualitative analysis of these extracts was done by using Thin Layer Chromatography (TLC) technique in order to observe the separation of the chemical compounds in the extracts. Ethanol crude extract was chosen to undergo the isolation process by using Column Chromatography (CC) technique as it showed the best separation of the chemical compounds. The chemical constituents isolated from ethanol crude extract were characterized using Ultraviolet-Visible (UV-Vis) Spectroscopy, Fourier Transform Infrared (FTIR) Spectroscopy and Gas Chromatography-Mass Spectrometry (GC-MS). Based on spectroscopy analysis, the isolated chemical constituents from ethanol extract of P. sarmentosum stems were probably identified as 3-( 4-methoxyphenyl) propionic acid and chaplupyrrolidone.